THE EFFECT OF QUALITY OF WORK LIFE AND JOB SATISFACTION ON WORK DISCIPLINE THROUGH SOCIAL SUPPORT AS AN INTERVENING VARIABLE IN THE FOOD AND BEVERAGES COMPANY PT FAMILY AURORA NUSANTARA - Syarifatul Wahidah; Hardani Widhiastuti; Rusmalia Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study aims to analyze the effect of Quality of Work Life and Job Satisfaction on employee Work Discipline, with Social Support as an intervening variable at PT Family Aurora Nusantara. This research employed a quantitative approach involving 89 employees selected through purposive sampling. Data were collected using questionnaires with a Likert scale. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results indicate that Quality of Work Life, Job Satisfaction, and Social Support have a positive and significant effect on Work Discipline. Furthermore, Quality of Work Life and Job Satisfaction also have a positive and significant effect on Social Support. The indirect effect analysis shows that Social Support mediates the relationship between Quality of Work Life and Job Satisfaction on Work Discipline. These findings suggest that improving employees' quality of work life and job satisfaction can strengthen social support in the workplace, which ultimately contributes to enhancing employee work discipline.